SEMIEMPIRICAL MOLECULAR-ORBITAL CALCULATIONS OF THE SUBSTITUENT EFFECTS ON ACYLATIONS OF 3-CEPHEM ANALOGS - CHANG, MH; KOH, HY; LEE, JC; LEE, YS (KOREAN CHEMICAL SOC, 1994)
Semiempirical MO calculations are applied to estimate the substituent effects on acylations of the nonfused N-vinyl-2-amino beta-lactams having frameworks analogous to 3-cephems. The stabilization energy for the reaction intermediate of the nucleophilic attack by the hydroxide ion is selected as the reactivity index and calculated by AM1 and PM3 methods for the model beta-lactams with substituents at the C1 and N-vinyl terminal positions. The reactivities are larger for -SH connected to the C1 and strong pi-acceptors at the N-vinyl terminal implying the large reactivity for known active cephalosporins. Quantum chemical calculation of stabilization energy could be useful in correlating antibiotic activities of many compounds obtained as derivatives of a lead compound.
Keywords: ANTIBACTERIAL ACTIVITY; CEPHALOSPORINS; PENICILLINS